Law Construction for ADIZ Implementation beyond the Airspace Sovereignty from the Perspective of Defense Strategy - et. al., Lidia Rina Dyahtaryani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A sovereign state in international law is a political entity that is represented by one centralized government that has sovereignty over a geographic area. International law defines sovereign states as having a permanent population, defined territory, one government and the capacity to enter into relations with other sovereign states . The components of the defined area or territory of a state are the terrestrial, fluvial, maritime and aerial domains. This leads to the larger scope of defense for a nation that includes the defense of its Land, Water and Airspace. One of the system used for the Airspace Defense is Air Defense Identification Zone (ADIZ) that is developed during the 1950s. ADIZ is used in the Korean War in 1951, to aid military forces in positive identification, location, and control of civil aircraft of non-hostile civil aircraft. In the modern world it is very important to have such system as part of a defense strategy, especially for a Country like Indonesia, with its huge aerial zone. However, until now there is no regulation by any international body nor any international treaty for the use of ADIZ in the airspace over land or water, or in regards of the Airspace Sovereignty.